The Impact of College Teaching on Students’ Academic and Labor Market Outcomes - Braga, Michela; Paccagnella, Marco; Pellizzari, Michele (Journal of Labor Economics, 2016)
This paper estimates the impact of college teaching on students’ academic achievement and labor market outcomes using administrative data from Bocconi University matched with tax records. The estimation exploits the random allocation of students to teachers in a fixed sequence of compulsory courses. We find that teacher effects on students' academic and labor market outcomes are only mildly positively correlated and that the professors who are best at improving the academic achievement of their students are not always also the ones who boost their earnings the most. For the least able students, the correlation between the academic and labor market effectiveness of teachers turns out to be negative.